2019
DOI: 10.3892/mmr.2019.10407
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA attenuates cerebral aneurysm formation by inhibiting the NF‑κB‑mediated inflammatory response

Abstract: The inflammatory response plays a vital role in cerebral aneurysm (CA) formation and progression. Tanshinone IIA (Tan IIA) is one of the major active components of Chinese medicine Danshen ( Salvia miltiorrhiza Bunge) and is widely used for the treatment of cardiovascular diseases, due to its anti-inflammatory effects. The aim of the present study was to investigate whether Tan IIA can attenuate CA formation in rat models, and determine its underlying mechanisms. CAs were induced in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Tan IIA protected H 2 O 2 ‐stimulated H9C2 cells and improved cardiac function in rats with heart failure through suppressing apoptosis and inducing autophagy via activation of the AMP‐activated protein kinase‐mammalian target of rapamycin pathway 42 . Tan IIA could suppress cerebral aneurysm formation through repressing the NF‐κB inflammation pathway in macrophages 43 . Tan IIA ameliorated nonalcoholic fatty liver disease in rats by inhibiting apoptosis, oxidative stress, and inflammation through down‐regulating toll‐like receptor 4/NF‐κB pathway and up‐regulating peroxisome proliferator‐activated receptor gamma pathway 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Tan IIA protected H 2 O 2 ‐stimulated H9C2 cells and improved cardiac function in rats with heart failure through suppressing apoptosis and inducing autophagy via activation of the AMP‐activated protein kinase‐mammalian target of rapamycin pathway 42 . Tan IIA could suppress cerebral aneurysm formation through repressing the NF‐κB inflammation pathway in macrophages 43 . Tan IIA ameliorated nonalcoholic fatty liver disease in rats by inhibiting apoptosis, oxidative stress, and inflammation through down‐regulating toll‐like receptor 4/NF‐κB pathway and up‐regulating peroxisome proliferator‐activated receptor gamma pathway 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Tanshinone IIA has neuroprotective effects against cerebral ischemia injury (Wang et al, 2014.;Chen et al, 2019). Over the past decade, Tanshinone IIA was demonstrated to have potential protective effects against cerebral ischemia-reperfusion injury through a variety of mechanisms (Zhu et al, 2017;Ma et al, 2019;He et al, 2020;Huang et al, 2020). Tanshinone IIA decreased the expression of cleaved caspase-3 protein and increased the expression of B-cell lymphoma 2 (bcl-2) protein in the ischemic cortex (Chen et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…These play a key role in atherosclerosis or aneurysm formation, including response to molecules of bacteria and KEGG analysis results. This suggests the presence of a chemokine signaling pathway, which may be involved in inflammatory response 20 . The GO and KEGG analysis results in the ruptured and unruptured groups suggested that angiogenesis and epithelial cell proliferation play important roles, possibly via the PI3K-AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%